Comprehensive characterization of tire and road wear particles in highway tunnel road dust by use of size and density fractionation. (September 2021) - Klöckner, Philipp; Seiwert, Bettina; Weyrauch, Steffen; Escher, Beate I.; Reemtsma, Thorsten; Wagner, Stephan
Abstract: Tire and road wear particles (TRWPs) are a major component of non-exhaust traffic emissions, but knowledge about their physico-chemical properties is limited. Road dust of a highway tunnel was fractionated by size and density, and fractions were analyzed for TRWPs, metals, seven tire tread indicator chemicals (benzothiazoles, 6-PPD and DPG) and effects in in-vitro bioassays. TRWP content in tunnel dust was very high (11–12%). The peak of the TRWP mass distribution was in the size fraction 20–50 μm, with 31–36% of the total TRWP mass and a content of up to 260 mg/g. The mass of organic tire constituents peaked in the smallest analyzed size fractions (<20 μm) with 35–55% of their total mass. They also peaked in the density fraction 1.3–1.7 g/cm³, indicating a lower TRWP density and a higher contribution of TP to TRWP (approx. 75%) than expected. Video-based shape analysis and SEM showed elongated particles, likely TRWPs, to be present in those size and density fractions ascribed to TRWPs by chemical analysis. But also irregular heteroagglomerates could be found. Solvent extracts of size and density fractions induced effects in bioassays indicative of the activation of the arylhydrocarbon receptor (AhR-CALUX) and the adaptive response to oxidative stress (AREc32). Similar comprehensive characterization of road dust from other sites may be needed to decide on whether TRWPs occurring in high concentrations in tunnel dust are suited as representative test materials for analytical purposes and TRWP fate studies. Graphical abstract: Image 1 Highlights: Tire and road wear particles (TRWPs) in tunnel dust: smaller and less dense than in road simulators. Mass distributions of tire constituents had maxima in the size fraction <20 μm. Density of TRWPs was mostly in the range of 1.3–1.7 g/cm³. Elongated particles were identified in size and density fractions. Solvent extracts of tunnel dust activated oxidative stress response in bioassays.